PENGARUH PROMOSI, HARGA, DAN PRODUK PT PEGADAIAN SYARIAH TERHADAP KEPUTUSAN MENJADI NASABAH TABUNGAN EMAS PADA MASA PANDEMI COVID-19 - Sopian, Ahmad Ali (UIN Sunan Gunung Djati Bandung, 2022)
The 2019 Corona Virus pandemic or better known as Covid-19 which began at the end of December caused problems in various economic sectors, including in Purwakarta Regency. However, there is a positive trend for precious metal investment through gold savings at PT Pegadaian Syariah Purwakarta which recorded an increase of 17.5 percent from the previous year. The purpose of this study was to analyze the magnitude of the promotion, price and product variables on the decision to become a gold savings customer. The study was conducted by quantitative descriptive method with a total sample of 92 people calculated using the Slovin formula with an error threshold of 10%. Based on the test results, the R squared value for the promotion variable is 0.534, the price variable is 0.457, and the product variable is 0.561. Thus, it is stated that the promotion has a significant effect of 53.4 percent, the price variable has an effect of 45.7%, and the product has an influence of 56.1%. The value of R Square for the three variables is 0.634, which means that the effect of X simultaneously is 63.4 percent. While the remaining 36.6 percent is caused by other variables that are not analyzed.